2016
DOI: 10.1002/ejp.868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pregabalin on the nociceptive, emotional and cognitive manifestations of neuropathic pain in mice

Abstract: Background Preclinical drug discovery for the treatment of chronic pain is at present challenged by the difficulty to study behaviours comparable to the complex human pain experience in animals. Several reports have demonstrated a frequent association of chronic pain in humans with affective disorders, such as anxiety and depression, and impaired cognitive functions, including memory and decision making, and motivation for goal‐directed behaviours. In this study, we validated different behavioural outcomes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 45 publications
4
29
1
Order By: Relevance
“…A partial reversal of thermal and mechanical hypersensitivity was shown after pregabalin self‐administration. This is in agreement with a number of publications assessing the antinociceptive effects of pregabalin in neuropathic pain models in rodents (Field et al., , ; Nozaki‐Taguchi et al., ; Kremer et al., ; La Porta et al., ). It has been suggested that pregabalin can activate the descending noradrenergic system to alleviate both mechanical and heat sensitivity associated with the nerve injury (Takeuchi et al., ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A partial reversal of thermal and mechanical hypersensitivity was shown after pregabalin self‐administration. This is in agreement with a number of publications assessing the antinociceptive effects of pregabalin in neuropathic pain models in rodents (Field et al., , ; Nozaki‐Taguchi et al., ; Kremer et al., ; La Porta et al., ). It has been suggested that pregabalin can activate the descending noradrenergic system to alleviate both mechanical and heat sensitivity associated with the nerve injury (Takeuchi et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, knockout mice for α2δ receptors, the main site of action of pregabalin, showed increased neuropathic mechanosensitivity, whereas thermal hyperalgesia was unaffected (Patel et al., ). In addition, pregabalin did not modify mechanical and thermal thresholds in sham‐operated mice, as expected from previous studies showing unchanged nociceptive thresholds after different pregabalin treatments (Kremer et al., ; La Porta et al., ).…”
Section: Discussionsupporting
confidence: 87%
“…La Porta et al (2016) reported ipsilateral mechanical and cold allodynia from day 3 to day 27 post-partial sciatic nerve ligation (PSNL) in Swiss albino male mice, with enhanced anxiety-like behavior in the elevated plus maze from 1 to 3 weeks post-PSNL and increased depressive-like behavior during FST, but only at 3 weeks post-PSNL. Also, a significant decrease in sucrose preference was observed from day 1 to day 20 post-PSNL.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of genetic inactivation of MOP and DOP on neuropathic pain manifestations were evaluated using a battery of tests to assess nociception, anxiety‐like behaviour, depressive‐like behaviour and long‐term memory, as previously reported (La Porta, Lara‐Mayorga, Negrete, & Maldonado, ; Liu & Chen, ). Briefly, animals were habituated three times on alternative days to the environment of nociceptive tests.…”
Section: Methodsmentioning
confidence: 99%